Clinicopathological correlation of infective vaginal discharges in non pregnant sexually active women of reproductive age group in a tertiary care centre of Western UP - Verma, Aruna; Gupta, Abhilasha; Goel, Swati; Garg, Amit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The aim was to study the etiology of infective vaginal discharges prevalent in our area and to study its association with PID. Methods: A total of 500 patients were recruited for study attending Gynae OPD and presenting with vaginal discharge. After detailed history taking and physical examination three sterile vaginal swabs were taken from the posterior fornix and sent for culture of Candida and Trichomonas on Saborauds Dextrose Agar and Kufperberg media respectively and one was used for smear for gram’s staining to diagnose Bacterial vaginosis by Nugent’s scoring. Results: In this study, prevalence of BV, Candida and Trichomonas vaginalis was found to be 146 (29.2%), 106 (21.2%) and 15(3%) respectively out of 24 cases had mixed infections while no organism was found in 257 cases (51.4%). Candida infection was found to be significantly associated with presence of other complaints such as itching, burning micturition, dyspareunia etc (p<0.001), curdy white discharge (p<0.001), thick consistency (p<0.001), presence of vulvitis (p<0.001) and pH 3.5-4.0 (p<0.0.001). Bacterial vaginosis was found to be significantly associated with underweights (p<0.004), cases with >1 abortions(p=0.015), presence of urogenital complaints (p<0.001), yellow/green (p<0.001) and purulent discharge (p=0.013), presence of malodour (p<0.001), thick consistency (p<0.001), moderate (p<0.001) and profuse (p=0.004) amount of discharge, vulvitis (p=0.001), cervical congestion (p=0.004), features of PID (p<0.001) and pH (4.6-5.0 & >5) (p<0.001). Trichomonas infection was found to be significantly associated with age group 31-35 (p=0.019), yellow/green vaginal discharge (p<0.001), presence of malodour (p=0.016), thick consistency of discharge (p=0.040), vulvitis (p<0.001) and pH>5 (p=0.004). Conclusions: Bacterial vaginosis and candidiasis are the most common causes of infective vaginal discharges in our community than trichomoniasis.